Methodical Approach to Estimating the Costs of Increasing Electricity Consumption in the Republic of Belarus in the Context of Nuclear Energy Development - T. G. Zoryna; A. A. Aliaksandrovich; V. Yu. Kondrusev; K. V. Starostenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of thisstudyis to estimate the costsofincreasing electricity consumptionin the Republic of Belarus for thelongtermin the context of the development of nuclearenergy. The initial data on various activities in the industrial sector (productivity, capital expenditures, increase in electricity consumption) were prepared based on the analysis of investment projects planned for implementation in the Republic of Belarus and foreign countries (mainly the Russian Federation). Toachieve this goal, an optimizationmodelwasbuilt. The optimizationcriterionis the minimization of capitalexpenditures for theimplementation of measurestoincrease electricity consumption while achieving its technicallypossiblepotential. The limitationswerethetechnicallypossiblepotential for increasing electricity consumption,aswell as the volumeofoutput. Based ontheoptimizationmodel, taking into accountvariations in inputparameters, scenarios have been developed that provide for an escalatingincrease in the volumeofproductsproduced in order to minimize the totalcostsofimplementing a set of measures. The simulationresultsshowedthat in order toincrease electricity consumptionfor a number of types of economicactivitiesin the industrialsector, the production of a particularcategory of productsmust be significantlyincreased.Thiscan, on theonehand,act as an instrument of import substitution(i.e., refusalofimportsupplies of thiscategory of products)and, on theotherhand,increase the exportpotential of industrialproducers of the Republic of Belarus.